Synthesising Resource-Advantage and Hofstede Cultural Dimensions: Customer Orientation, Knowledge Creation and Firm Performance - Liow, Melissa Li Sa (ASEAN Journal on Hospitality and Tourism, 2021)
There is a dearth of studies on synthesising the resource-advantage theory and Hofstede cultural dimensions that explore the influence of customer orientation and knowledge creation on the firm performance for small hotels. This paper reviews extant literature that provides insights on the influence of customer orientation and knowledge creation on firm performance. In-depth interviews with three hotel owners and three hotel managers were performed in this study. The results disclose that forging memorable and positive customer experiences and developing informed knowledge databases are business practices that sustain the firm performance. From the theoretical aspect, it is a preliminary step to blend the culturally relevant customer orientation and knowledge creation elements into forming a firm performance framework designed for small hotels.